Proven Delivery Models for LED Public Lighting : Joint Procurement Delivery Model - Ontario, Canada - Makumbe, Pedzisayi (World Bank, Washington, DC, 2016)
The context in Ontario was encouraging for light-emitting diode (LED) programs at federal, provincial, and municipal levels. At the federal level, there were a number of incentive programs funded by the federal gas tax that municipalities tapped into for municipal energy efficiency retrofits and upgrades. The federal gas tax and a yearly transfer from the Government of Canada to each municipality based on population; it is an environmental measure aimed at reducing greenhouse gases. Independent electricity system operator (IESO) has a comprehensive master plan with ambitious energy efficiency goals, implemented with both environmental and economic rationales in mind. IESO’s conservation first framework, developed in 2014, maps out Ontario’s energy conservation goals from 2014 to 2020, emphasizing a coordinated effort within all stages of energy planning, as well as more effective teamwork among sector partners, particularly in support of local distribution companies (LDCs). The global adjustment mechanism fund covers various initiatives, including the province’s energy conservation and demand management programs. As part of this commitment to energy conservation, IESO provides very significant fiscal incentives of up to 30 percent for energy efficiency in the form of energy efficiency infrastructure rebates through a program called save on energy. It is possible that IESO will lower the amount of the outdoor lighting incentive, as it is known, to reflect the growing cost-competitiveness of LEDs in the market without incentives.